Market shares, instability and revealed comparative advantage of seafood exports from India - Pavithra, S.; Ananthan, P. S.; Krishnan, M. (Indian Journal of Fisheries, 2014)
The present study analysed the export competitiveness of Indian shrimp. The index of instability for the overall seafood exports from India was 0.17 for the period 1991-2010. Shrimp is the major seafood export item of India with a growth rate of 2.89% and 10.47% in terms of quantity and value of exports respectively, during 1991-2011. Share of Indian shrimp in the world market declined slightly from 7.01% in 1990-1992 to 6.25% in 2008-2010 while the shares of China, Vietnam, Thailand and Indonesia increased owning to value addition and re-export of processed shrimp from these countries. Unit value realisation for Indian shrimp was US $ 5.69 per kg in 2009. All the major exporting countries experienced a decline in the unit value realisation due to changing supply- demand pattern and global slowdown. Export competitiveness index for Indian shrimp remained at 1.00 following a decline in the past few years. Revealed competitiveness index for Indian shrimp was 1.65 in the year 2009 indicating a comparative advantage of the country in shrimp exports. Processing, value addition and compliance with the changing international quality standards are the crucial areas for enhancing and sustaining the competitive position of Indian shrimp in the world market.